ADVANCES IN CRYOGENIC FRACTURING OF COALBED METHANE RESERVOIRS WITH LN2 - Longinos, Sotirios Nik.; Wang, Lei; Hazlett, Randy (Energies, 2022)
Coalbed methane (CBM) is a significant unconventional natural gas resource existing in matrix pores and fractures of coal seams and is a cleaner energy resource compared to coal and crude oil. To produce CBM, stimulation operations are required, given that the coal permeability is generally too low. Hydraulic fracturing is the most widely used technology for reservoir stimulation; however, there are a few challenging issues associated with it, e.g., huge water consumption. In the past decade, the use of liquid nitrogen (LN2) as a fracturing fluid has been intensively studied for stimulating CBM reservoirs, achieving considerable progress in understanding fracturing mechanisms and optimizing fracturing techniques. This paper presents a thorough review of experimental design and observations, modeling procedures and results, field applications, and published patents. Existing studies are divided into five different groups for discussion and comparison, including immersion tests, injection tests, jet drilling tests, numerical modeling, and field applications. Based on the comprehensive evaluation of the outcomes, it is obvious that cryogenic fracturing using LN2 is a promising eco-friendly fracturing technique that can effectively enhance coal rock permeability to increase the production of CBM.
Keywords: Type of access: Open Access; cryogenic fracturing; coalbed methane; immersion tests; injection experiments; numerical modeling